A discussion forum on managerial interpersonal skills. Issue 5 (13th June 2016) - Beenen, Gerard; Pichler, Shaun
Abstract : Purpose: – Managerial interpersonal skills (MIPS) are widely considered important for management development, yet the nature of MIPS has eluded researchers. The purpose of this paper is to propose five MIPS core skills, giving attention to the role of context, the relationship of MIPS to traits, and implications for training design, assessment and evaluation. Design/methodology/approach: – The authors interweave a discussion forum of domain experts (Hillary Anger-Elfenbein, Timothy Baldwin, Paulo Lopes, Bronston T. Mayes, Ronald Riggio, Robert Rubin and David Whetten) with research commentary and implications for management development. The discussion focussed on: first, how do we define MIPS? Second, how important is context for defining, assessing or developing MIPS? Third, are MIPS traits, or skills that can be developed? Findings: – The authors propose MIPS include five core skills that sequentially build upon one another: managing-self, communicating, supporting, motivating and managing conflict. Although context may impact the importance of each skill across cultures, situations and jobs, the authors offer these skills as a useful starting point for MIPS assessment, training design and evaluation. Research limitations/implications: – The proposed five core skill model for MIPS needs further research and psychometric validation. Originality/value: – By proposing MIPS include five specific trainable skills that are relevant across contexts, this paper advances MIPS research, assessment and development.